AI in Islamic finance: Global trends, ethical implications, and bibliometric insights - Iqbal, Muhammad Saeed; Sukamto, Fifi Anti Mapika Sari Binti; Norizan, Siti Noraisyah Binti; Mahmood, Shanayyara; Fatima, Arooj; Hashmi, Faiza (Center for Islamic Economics and Development Studies [P3EI], 2025)
Purpose – This study explores the integration of Artificial Intelligence (AI) in Islamic finance, analyzing global trends, ethical implications, and future research directions. The purpose is to assess AI’s role in enhancing Sharia compliance, regulatory adherence, and operational efficiency in Islamic financial institutions.Methodology – Using a bibliometric analysis approach, this research examines publications from 2010 to 2023 indexed in Scopus and Web of Science. Keywords such as Islamic finance,